Eyewitness to a Genocide : the United Nations and Rwanda The United Nations and Rwanda - Barnett, Michael (Ithaca : Cornell University Press, 2003)
Why was the UN a bystander during the Rwandan genocide? Do its sins of omission leave it morally responsible for the hundreds of thousands of dead? Michael Barnett, who worked at the U.S. Mission to the United Nations from 1993 to 1994, covered Rwanda for much of the genocide. Based on his firsthand experiences, archival work, and interviews with many key participants, he reconstructs the history of the UN's involvement in Rwanda.
Trade
Keywords: United Nations; Genocide; Rwanda; Africa -- Ethnic Relations